2017
DOI: 10.2967/jnumed.116.187211
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Clearance in Alzheimer Disease Measured with Dynamic PET

Abstract: Evidence supporting the hypothesis that reduced cerebrospinal fluid (CSF) clearance is involved in the pathophysiology of Alzheimer disease (AD) comes primarily from rodent models. However, unlike rodents, in which predominant extracranial CSF egress is via olfactory nerves traversing the cribriform plate, human CSF clearance pathways are not well characterized. Dynamic PET with 18 F-THK5117, a tracer for tau pathology, was used to estimate the ventricular CSF time-activity as a biomarker for CSF clearance. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
184
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 194 publications
(193 citation statements)
references
References 38 publications
6
184
3
Order By: Relevance
“…However, mice lacking functional vascular endothelial growth factor receptor 3 (VEGFR3), a critical regulator of lymphangiogensis, develop LN hypoplasia and demonstrate decreased clearance of tracers injected into the brain(95). Reduced CSF clearance at the nasal mucosa in humans has also been linked to AD and increased Aβ burden(97). These data suggest that disruption of peripheral efflux sites significantly affect CNS solute clearance.…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…However, mice lacking functional vascular endothelial growth factor receptor 3 (VEGFR3), a critical regulator of lymphangiogensis, develop LN hypoplasia and demonstrate decreased clearance of tracers injected into the brain(95). Reduced CSF clearance at the nasal mucosa in humans has also been linked to AD and increased Aβ burden(97). These data suggest that disruption of peripheral efflux sites significantly affect CNS solute clearance.…”
Section: Glymphatic Systemmentioning
confidence: 99%
“…Some of those, such as lactate, tau, and Aβ, have been implicated in dementia development [90,140,141]. In addition to being a consequence of Aβ pathology, impairments in CSF clearance and the glymphatic system could promote Aβ accumulation [15,142]. By using in vivo MRI of gadolinium-based contrast agent injected into the CSF, Gaberel and collaborators found that ischemic stroke in rodents leads to a decrease of CSF circulation through perivascular spaces, which could be explained by a decrease of arterial pulsation after artery occlusion [17,143].…”
Section: Glymphatic System Impairmentmentioning
confidence: 99%
“…Given the close connection between CSF flow and the glymphatic system, 11 C-PiB PET could also serve as an in-vivo marker of glymphatic system function. Here we aim to replicate previous results that showed decreased lateral ventricular 11 C-PiB signal magnitude in Alzheimer's disease compared to controls (19) and to extend the method to mild cognitive impairment and multiple sclerosis patient groups.…”
Section: Introductionmentioning
confidence: 75%
“…Standardized uptake value ratios (SUVRs) from 50 to 70 minutes were calculated for the gray matter and lateral ventricle ROIs for each subject from both datasets using cerebellum or a supervised reference region for the AD/MCI and multiple sclerosis datasets, respectively. For consistency with a previous study (19), area-under-curve (AUC) from 35 to 80 minutes was also calculated for the lateral ventricle ROI for a subset of the AD/MCI dataset. AUC35-80 was also calculated for the lateral ventricle ROI for all subjects in the multiple sclerosis dataset.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation